Synthesis of a novel reactive type flame retardant composed of phenophosphazine ring and maleimide for epoxy resin. (July 2019) - Luo, Qinqin; Sun, Yulin; Yu, Biao; Li, Chengpeng; Song, Jiangli; Tan, Dexin; Zhao, Jianqing
Abstract: It is well known that the high loading of flame retardants is needed to improve the flame-retardant property of epoxy resins accompanied with the serious deterioration of their thermal and mechanical properties. A novel flame retardant with the high flame-retardant effect, namely 1-(4-hydroxyphenyl)-3-(10-oxido-5H-phenophosphazine-10-yl) pyrrolidine-2, 5-dione (DPPA-HPM), was synthesized to solve the problem. The nuclear magnetic resonance and high-resolution electrospray ionization mass spectrometry verified the successful synthesis of DPPA-HPM. DPPA-HPM was an efficient flame retardant for epoxy resin. Only 1.5 wt% loading of DPPA-HPM was found to endow the epoxy resin with UL-94 V-0 rating and the high limited oxygen index value of 29.5%. Moreover, the flame-retarded epoxy resin possessed the good comprehensive properties with the maintained glass transition temperature and the improved ﬂexural strength as compared with the control epoxy resin, which exhibits good potential application prospects. Highlights: A novel environment-friendly halogen-free flame retardant for epoxy resins, namely DPPA-HPM, was successfully synthesized. Only 1.5 wt% loading of DPPA-HPM was found to endow epoxy resin with UL-94 V-0 rating and the high LOI value of 29.5%. Compared with the control epoxy resin, the flame-retarded epoxy resin possessed the good comprehensive properties.